2010
DOI: 10.1212/wnl.0b013e3181e0438b
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and melatonin levels following traumatic brain injury

Abstract: Objectives: Sleep disturbances commonly follow traumatic brain injury (TBI) and contribute to ongoing disability. However, there are no conclusive findings regarding specific changes to sleep quality and sleep architecture measured using polysomnography. Possible causes of the sleep disturbances include disruption of circadian regulation of sleep-wakefulness, psychological distress, and a neuronal response to injury. We investigated sleep-wake disturbances and their underlying mechanisms in a TBI patient sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(171 citation statements)
references
References 43 publications
8
156
3
3
Order By: Relevance
“…Poor subjective sleep quality is one of the most common complaints of patients who have experienced mTBI, with milder injury being associated with greater impairments in both subjective and objective measures of sleep [22]. Furthermore, the incidence of sleep disorder diagnoses is greater in patients with mTBI than in the general population.…”
Section: Essential Questions Related To Mtbi and Sleep Why Does Sleepmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor subjective sleep quality is one of the most common complaints of patients who have experienced mTBI, with milder injury being associated with greater impairments in both subjective and objective measures of sleep [22]. Furthermore, the incidence of sleep disorder diagnoses is greater in patients with mTBI than in the general population.…”
Section: Essential Questions Related To Mtbi and Sleep Why Does Sleepmentioning
confidence: 99%
“…More specifically, patients with mTBI demonstrate increased sleep fragmentation, delayed sleep onset, increased awakenings and time awake during the night, and reduced sleep efficiency (e.g., [81]). Further, at least 3 studies have found that relative to matched healthy controls, patients with mixed-severity TBI demonstrate increased slow-wave sleep (SWS) [22,82], although another study found reduced SWS and lower NREM delta power [83]. In light of the regenerative effects of SWS (e.g., axonal sprouting and synaptic remodeling), these findings appear to suggest a potential role for SWS in recovery from TBI.…”
Section: What Sleep Disorders Occur Following Mtbi?mentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of damage to sleep-wake regulating centers such as the ascending reticular formation and associated pathways or neurotransmitter systems affect sleep disturbances [10,11]. Anxiety and depression frequently occur after TBI, and increased depression is associated with decreased sleep quality [12,13].…”
Section: Introductionmentioning
confidence: 99%